Assessment of ICT Skills Application of Teacher Educators in Kwara State Colleges of Education, Nigeria - Oluwatoyin, Fashiku Christopher; Abiola, Yusuf Abubakar; Francis, Olowo Busuyi; Oba Baba, Ayoku; Comfort, Fashiku Bunmi (Innovare Journal of Education, 2022)
The study was carried out to assess the Information and Communication Technology (ICT) skills application of teacher educators in Kwara State Colleges of Education, Nigeria. The descriptive survey research design was adopted; the population of the study comprised 430 lecturers from Kwara State Colleges of Education Oro, Lafiagi, and Ilorin, respectively. A proportional sampling technique was used to select 160 respondents from the two teacher educator institutions. A simple random sampling technique was used in selecting 60 respondents from Oro College of Education and 100 respondents from Kwara State College of Education Ilorin. One self-designed questionnaire titled ‘Assessment of ICT Competency Skills of Lecturers’ (AICTCSL) with four points Liker scale was used to elicit information from the respondents. The instrument was validated. Its reliability was ensured at .78. Total Average Weighted Response (TAWR), and percentage and frequency counts were used in analyzing the collected data for the raised research questions at .05 levels of significance, while z-test statistics were used in addressing the formulated hypotheses. It was discovered in the study that lecturers in the used institutions were competent in manipulating the computer keyboard and connecting to the internet but were not competent in accessing the information on CD, organizing electronic files into folders, use of application software, use of PowerPoint, word excel and blog website. Also, no significant difference was established between the mean scores of lecturers in Kwara State Colleges of education Oro and Ilorin on their ICT skills acquisition and use, while there was a significant difference in the mean ratings of teacher educators from Oro and Ilorin on their use of application software competency. It was therefore recommended that government should make it a matter of policy that all lecturers in the institutions are ICT literate and it should be a prerequisite for their promotion and recruitment for a lecturing job in the state.